2019
DOI: 10.1016/j.cub.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Chordate Telencephalon

Abstract: The dramatic evolutionary expansion of the neocortex, together with a proliferation of specialized cortical areas, is believed to underlie the emergence of human cognitive abilities. In a broader phylogenetic context, however, neocortex evolution in mammals, including humans, is remarkably conservative, characterized largely by size variations on a shared six-layered neuronal architecture. By contrast, the telencephalon in non-mammalian vertebrates, including reptiles, amphibians, bony and cartilaginous fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 193 publications
(264 reference statements)
3
73
0
1
Order By: Relevance
“…Phylogenetic comparative analyses on vertebrate telencephalon evolution are not uncommon. For instance, the neocortex makes up the majority of the telencephalon in primates (Briscoe & Ragsdale, 2019). Group social complexity, diet and cognitive performance are positively associated with neocortex size in this taxon (Shultz & Dunbar, 2010; Reader, Hager & Laland, 2011; DeCasien & Higham, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic comparative analyses on vertebrate telencephalon evolution are not uncommon. For instance, the neocortex makes up the majority of the telencephalon in primates (Briscoe & Ragsdale, 2019). Group social complexity, diet and cognitive performance are positively associated with neocortex size in this taxon (Shultz & Dunbar, 2010; Reader, Hager & Laland, 2011; DeCasien & Higham, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the light of recent studies that revealed several homologies between pallial and subpallial areas in fish and mammals (Briscoe & Ragsdale, 2019; Ganz et al, 2012; Giassi, Duarte, et al, 2012; Giassi, Ellis, & Maler, 2012; Giassi, Harvey‐Girard, et al, 2012; Harvey‐Girard et al, 2012; Nieuwenhuys, 2009; Wullimann & Mueller, 2004), it is worth mentioning that, in areas ascribed to the dorsal telencephalon (Giassi, Duarte, et al, 2012; Giassi, Ellis, & Maler, 2012; Giassi, Harvey‐Girard, et al, 2012; Harvey‐Girard et al, 2012), no ChAT‐positive cells were detected. This situation is similar to that described for the pallium of most other fish species (Lopez et al, 2012; López et al, 2013; Morona et al, 2013; Mueller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrate pallium is considered essential for advanced cognitive abilities. Unlike other sectors of the vertebrate brain, the cytoarchitecture and elaboration of pallial domains vary immensely across vertebrate classes, and even within closely related taxa 1 . In mammals, for example, dorsal pallium develops into a six-layered structure called neocortex, the elaboration of which is associated with advanced cognitive abilities 2,3 .…”
Section: Main Textmentioning
confidence: 99%
“…In mammals, for example, dorsal pallium develops into a six-layered structure called neocortex, the elaboration of which is associated with advanced cognitive abilities 2,3 . In cartilaginous fishes, some taxa have a layered pallium, while in other species the organization of pallium is not at all obvious, and difficult to separate from subpallial structures 1 . Large swaths of bird pallium are unlayered 4,5 (Fig.…”
Section: Main Textmentioning
confidence: 99%